Post-Liberal Peace Transitions Between Peace Formation and State Formation - Richmond, Oliver P. (Edinburgh University Press, 2022)
Explores the interplay of forces that shape 'peace formation' in modern conflict-affected statesWhy is it that states emerging from intervention, peacebuilding and statebuilding over the last 25 years appear to be 'failed by design'? This study explores the interplay of local peace agency with the (neo)liberal peacebuilding project. And it looks at how far can local 'peace formation' dynamics can go to counteract the forces of violence and play a role in rebuilding the state, consolidate peace processes and induce a more progressive form of politics. By looking at local agency related to peace formation, Oliver Richmond and Sandra Pogodda find answers to the pressing question of how large-scale peacebuilding or statebuilding may be significantly improved and made more representative of the lives, needs, rights, and ambitions of its subjects.Key FeaturesComparative case studies, based on wide-ranging fieldwork, look at Afghanistan, Bosnia and Herzegovina, Cambodia, Cyprus, East Timor (Timor-Leste), Israel-Palestine, Kosovo, Northern Ireland, Sierra Leone and the Solomon IslandsTakes an innovative theoretical approach, engaging with local and contextual forms of peacebuilding agency and including local authorsContinues the project begun in Oliver Richmond's 2009 book Liberal Peace Transitions